Q: 9 square root 4 minus 12 square root 4?

Write your answer...

4 x square root of 10 minus square root of 10 = 3 x square root of 10.

The square root of -4 is: 2 i

JACK

2 square root 2

It is imaginary; we denote sqrt of -1 = i square root (-4) = ± 2i

8

The square root of 12 equals the square root of 4 times 3. The square root of 4 is 2. The square root of 12 equals 2 times the square root of 3.

X2+5x-6. a=1, b=5, and c=-6 The formula is: -b plus or minus the square root of b squared minus 4ac all over 2a. -b+square root of b2-4ac ---- 2a -5 plus or minus the square root of 5 squared minus 4(1)(-6) -5 plus or minus the square root of 25-4(-6) -5 plus or minus the square root of 25+24 -5 plus or minus the square root of 49 -5 plus or minus 7 Here is where you split into two different answers: Number 1: -5 plus 7= 2 Number 2: -5 minus 7= -12 Your answer is X=2, -12

It depends on whether you take the positive square root of 4 (YES) or the negative square root of 4 (No).

4 times 4 minus 4 minus square root of 4.

?

x plus the square root of 2

To simplify the square root of 12: Look at numbers that can be reduced from the larger number and can be square rooted itself. 4 * 3 = 12 The square root of 4 is 2. Therefore the simplification of the square root of 12 is: 2*square root of 3

29.5

4 sqrt(3) is. 8 of anything, minus 4 of the same thing, always leaves 4 of them.

sqrt(12) - sqrt(48)= sqrt(12)- sqrt (12 x 4)= sqrt(12)- sqrt (12 ) x 2= -sqrt(12)= -(sqrt(4 X 3))= -2 X SQRT (3)

The answer is 2i. When dealing with negative square roots, the expression i is used to represent the square root of -1.

3

It is: (3*2)-(2*2) = 2

hmm... okay, if I understand you correctly, 2 times the square root of 3 times the square root of 12? = 2(1.73)(3.46) = 11.9716. If you aren't using the approximations, then just simplifying is... [sorry, I can't do the square root sign on the computer...] 2(square root of 3)(square root of 12) = 2(square root of 3)(square root of 4*3) = 4(square root of 3)(square root of 3) = 4(3) = 12!!! HOPE I HELPED!! :-)

3

In order to represent the square root of a minus number (which does not in fact actually exist other than as an abstract notion), mathematicians use an imaginary number called "i". i represents the value of the square root of -1. We must remember that it is not a real number, which is why we call it imaginary.So to answer your question, i, or a multiple of i, times itself equals a minus number.For example 2i * 2i = -4 (this is because we can rewrite -4 as 4 * -1. The square root of 4 is 2 and the square root of -1 is i. Therefore the square root of -4 is 2i).

(3 x 2) - (2 x 2) = 2

The square root of 25a squared is 5a. The square root of 16 is 4.So the answer is (5a+4)(5a-4)

bbb